Factors influencing Escherichia coli O157 colonization of the gastrointestinal tract of feedlot cattle - Aperce, Celine C. (Kansas State University, 2012)
The first chapter of this dissertation reviews factors affecting E. coli O157:H7 prevalence in the gastrointestinal tracts of cattle. Chapter 2 assessed E. coli O157:H7 ability to use bovine intestinal mucus and its constituents as substrates for growth in vitro in the presence and absence of fecal inoculum and exogenous enzymes. Whole mucus supported the greatest pathogen growth (P < 0.05), but all components tested were able to sustain E. coli growth. Chapter 3 evaluated the impact of crude glycerin feeding on E. coli O157 fecal shedding by cattle fed growing and finishing feedlot diets with corn or a combination of corn, distiller’s grains, and soybean hulls. Increasing levels of crude glycerin decreased incidence of E. coli O157 in growing cattle (linear effect, P < 0.01) and tended to do so in finishing cattle fed corn-based diets (P < 0.06). No effect of glycerin was observed in finishing cattle fed the byproduct-based diets (P > 0.05), highlighting potential for glycerin use as a means for controlling fecal prevalence of E. coli O157 in cattle fed conventional grain-based diets. Chapter 4 evaluated transportation and lairage effects on fecal shedding of E. coli in feedlot cattle by mimicking transport to the abattoir. Shedding patterns were influenced by transportation, with significantly lower E. coli O157 prevalence in transported animals 4 hours after transit (P < 0.05). Additional post-transit samplings are, however, needed to confirm effects of transport stress on pathogen prevalence and shedding patterns. The experiment summarized in chapter 5 evaluated the potential for utilizing fecal long-chain fatty acid (LCFA) profiles as an indicator of E. coli O157 status. Out of 39 LCFA evaluated, only eicosapentaenoic acid (EPA) concentration was associated with presence of the pathogen (P < 0.02). The final chapter assessed the impact of dietary menthol, up to 0.3% of diet DM, on antimicrobial resistance in commensal E. coli. Menthol addition affected prevalence of tetracycline resistant E. coli, but contrary to our hypothesis, increased their occurrence after 30 days of treatment (P < 0.006). No hypothesis on mechanism responsible for this increase could be made from the present study.
Keywords: Escherichia coli; Feedlot; Animal Sciences (0475)